Enhancing Senior High School Students’ English Basic Grammar Skills Through Task- Based Learning - Pemina Br Sembiring; Tengku Silvana Sinar; Deliana; Rahmadsah Rangkuti; Rahmah Fitriani (Universitas Pendidikan Ganesha, 2026)
Grammar instruction in EFL classrooms remains predominantly dominated by conventional teacher-centered methods and rote memorization, which hinder students’ ability to apply grammatical knowledge in authentic communicative contexts. This condition leads to students’ low proficiency in understanding and using parts of speech contextually. This study aims to identify the most engaging stages of Task-Based Learning (TBL), describe the implementation of TBL in grammar instruction, and explain the underlying reasons for its effectiveness. This research adopts a mixed-method approach with a quasi-experimental design employing a one-group pre-test–post-test model. The participants consisted of 25 eleventh-grade senior high school students, who also served as the main subjects in the instructional implementation. Data were collected through classroom observations, student feedback, and assessments of grammatical competence. The findings reveal that students demonstrated a significant improvement in their ability to use parts of speech accurately when grammar was taught through contextualized tasks rather than isolated rule explanation. Additionally, students exhibited increased motivation, participation, and confidence during task-based activities. The study concludes that Task-Based Learning effectively enhances grammatical competence by promoting active language use, interaction, and reflection. The findings imply that grammar instruction should be oriented toward a communicative, task-based approach to improve the quality of language learning. Furthermore, teachers are recommended to systematically integrate TBL into their instructional practices to support the development of more applicable and functional language competence.